American dream e o pesadelo vermelho: americanização e anticomunismo nas páginas de O Cruzeiro 1947-1950 - Mendes, Lilian Marta Grisolio (2011)
The present essay aims at analyzing one of the most important 20th Century Brazilian magazines, namely O Cruzeiro. The reflection hereby proposed encompasses the discussion about the option for capitalist modernity based on the North-American model to the detriment of the communist option which presents itself in the post-war period. Thus, we mean to render problematic ideological rather than merely informative reports since they disclosed the ideas that tried to adjust society as well as the national politics between 1947 and 1950. Our goal consists of trying to understand the basis underlying the discourse that promoted the Brazilian modernization, heavily shaped by the North-American model, and which defended a kind of development for society underlined by Americanized values at every social level, from economic to cultural issues, thus rejecting any project that even remotely resembled communist principles. As a direct consequence of assuming such a posture, the magazine produced an intense anti-communist discourse which sometimes identified the Stalinist soviet regime as dangerous and perverse and, at other times, portrayed it as a world of sadness and suffering. Taking the American democracy as a model and fighting against communism, the magazine promoted a certain kind of modernization. The understanding of the intense combat against the Varguista project belongs to this sphere. That project is totally against the idea that modernization would derive from an intrinsic subordination to international funds. Therefore, the nationalistic project was identified by the magazine as outdated, representing tardiness. Although the magazine strongly opposed to the election of Getúlio Vargas in the 1950 elections, it was defeated. Studying the magazine historicity, we disclose an intense effort to identify the United States of America as the ideal partner regarding the construction of a society guided by consumption. In the 1940s, Brazil was still looking for a model for its development and the magazine O Cruzeiro was clearly the one which best spread North-American values via its weekly publication. Thus, O Cruzeiro intentionally contributed to the building of the principles underlying the American Dream as well as the fight against the Red Scare